Automatic 2D line extraction from 3D geometric model - Hu, Yunwen. (2009)
A new approach that extracts outlines from 3D geometric models is investigated. A 3D model is created in Maya based on 2D designs provided by artists. Outlines, including occluding contour, suggestive contour, and boundary, that contain shape information of the model are examined mathematically. APIs in RTSC, Trimesh, and OpenGL are applied to extract the outlines from the model and project them onto 2D planes. Hidden lines and redundant points in the projected results are removed to produce more accurate and compact shape information. Finally, similarity comparison is performed between the results and the original 2D drafts by using shape matching algorithms.